2018
DOI: 10.1007/978-3-319-73848-2_36
|View full text |Cite
|
Sign up to set email alerts
|

Sublinear Expectations: On Large Sample Behaviours, Monte Carlo Method, and Coherent Upper Previsions

Abstract: Shige Peng's sublinear expectations generalize ordinary linear expectation operators. It is shown that the behaviour of sample averages of Peng i.i.d. variables may be very different from the probabilistic intuition. In particular, Peng's generalization of the Monte Carlo method is shown to be wrong. It is also observed that sublinear expectations coincide with Peter Walley's coherent upper previsions on a linear space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Note that, as τ is quasicontinuous, it follows by Corollary 2.17 that 2 and by using the same arguments as in (4. 19)-(4.20) we get by (4.28) that…”
Section: Feynman-kac Formula In the G-settingmentioning
confidence: 83%
See 1 more Smart Citation
“…Note that, as τ is quasicontinuous, it follows by Corollary 2.17 that 2 and by using the same arguments as in (4. 19)-(4.20) we get by (4.28) that…”
Section: Feynman-kac Formula In the G-settingmentioning
confidence: 83%
“…By using Theorem 4.11 we are able to numerically approximate the G-conditional expectation in (1.1) in a computationally efficient way without resolving to Monte Carlo methods. This is also a further contribution since it is well known that the strong law of large numbers in the G-setting differs from the one in the classical framework, see Theorem 3.1, Chapter II in [16], and this may cause some issues in the application of Monte-Carlo algorithms, see for example [19].…”
Section: Introductionmentioning
confidence: 99%
“…Terán [19] showed that (2.2) and (2.5) don't hold in general by a counterexample in which µ = E[X 1 ] = 0, µ = E[X 1 ] = 1 and S n (ω)/n → 0 for all ω ∈ Ω. Zhang [21] pointed out that, under the framework of sub-linear expectation, the continuity of the capacity is a very strict condition by showing that, if a capacity V which satisfies (1.5) is continuous and there is a sequence…”
Section: The Main Resultsmentioning
confidence: 99%
“…For (2.8), the condition (CC) is not needed. The counterexample given by Terán [19] shows that (2.9) and (2.10) may fail if the condition (CC) is not satisfied (c.f. Theorem 3.1 of [19]).…”
Section: The Main Resultsmentioning
confidence: 99%
“…Example 5.2 Let Ω be the same space as is defined in Example 5.1, and let Ω 0 be the subset of Ω with ξ i = 0 for all except a finite number i ∈ N. i) ( [16])…”
mentioning
confidence: 99%